Wielkomiejskie zespoły mieszkaniowe jako środowisko życia - Barczykowska, Agnieszka (Wydawnictwo Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2009)
The first house built in the prefabricated concrete technology was built in 1957 in Jelonki near Warsaw. This method started to develop at the end of the 60s and expanded dynamically. In the buildings from concrete units still live about 8 million people. Nowadays this technology is criticized and a question appears: "Is it an optimal habitat to live?" Many people say: "No". I would like to show that houses from the prefabricated concrete units have some advantages too. In my article I try to analyze comprehensively the "quality of life" of the inhabitants of buildings from the prefabricated concrete units.
Keywords: środowisko lokalne; blokowisko; wielkie miasto; system wychowawczy; problem społeczny